Immunological analysis of the aqueous humour in candida endophthalmitis. I: Experimental study. Issue 4 (April 1988) - Malecaze, F.; Bessieres, M. H.; Bec, P.; Fleutiaux, S.; Mathis, A.; Seguela, J. P.
Abstract : An immunological study of aqueous humour and serum was carried out in experimental ocular candidosis in rabbits. Anti-candida antibody titres, immunoglobulin G, and albumin levels were evaluated in the aqueous humour and in the serum. A local synthesis of anti-candida antibodies was detected in numerous rabbits at the height of clinical activity of the lesions.